Jaundice and life‐threatening hemobilia: An uncommon presentation of choledochal cyst. Issue 8 (4th July 2013) - Koh, Peng Soon; Yoong, Boon Koon; Vijayananthan, Anushya; Nawawi, Ouzreiah; Mahadeva, Sanjiv
<x xml:space="preserve">Abstract</x> Hemobilia with jaundice as a result of cholestasis and bleeding from choledochal cyst is uncommon. Ascertaining the diagnosis is often challenging and delayed diagnosis can lead to significant consequences due to hemodynamic instability, particularly in elderly patients. Although surgery remains the definitive treatment modality, interventional radiology for hemostasis has been increasingly recognized as an option. In this manuscript, we described two Malaysian cases of jaundice and hemobilia associated with choledochal cysts and the challenges related with clinical diagnosis and management.